Deconstructing the Antiviral Neutralizing-Antibody Response: Implications for Vaccine Development and Immunity - VanBlargan, Laura A. (Microbiol Mol Biol Rev, 2016)
The antibody response plays a key role in protection against viral infections. While antiviral antibodies may reduce the viral burden via several mechanisms, the ability to directly inhibit (neutralize) infection of cells has been extensively studied. Eliciting a neutralizing-antibody response is a goal of many vaccine development programs and commonly correlates with protection from disease. Considerable insights into the mechanisms of neutralization have been gained from studies of monoclonal antibodies, yet the individual contributions and dynamics of the repertoire of circulating antibody specificities elicited by infection and vaccination are poorly understood on the functional and molecular levels. Neutralizing antibodies with the most protective functionalities may be a rare component of a polyclonal, pathogen-specific antibody response, further complicating efforts to identify the elements of a protective immune response. This review discusses advances in deconstructing polyclonal antibody responses to flavivirus infection or vaccination. Our discussions draw comparisons to HIV-1, a virus with a distinct structure and replication cycle for which the antibody response has been extensively investigated. Progress toward deconstructing and understanding the components of polyclonal antibody responses identifies new targets and challenges for vaccination strategies.